Global key concepts of civil-military cooperation for disaster management in the COVID-19 pandemic—A qualitative phenomenological scoping review - Ries, Markus (Frontiers in Public Health, 2022)
Background: In the context of a holistic and comprehensive disaster response effort to the COVID-19 pandemic, many countries across the globe mobilized their military forces in order to cope with sudden and exponential surges of critically ill patients with COVID-19 in stretched healthcare systems. Objective: The purpose of this work is to identify, map, and render world-wide key concepts of civil-military cooperation (CIMIC) in disaster management during the COVID-19 crisis visible. Material and Methods: Literature was systematically searched in three databases (PubMed, Web of Science, Cochrane Library) on 26 January 2022, and analyzed with qualitative, mixed narrative-phenomenological methods in compliance with PRISM-ScR and SRQR. Results: Forty-five publications were included in the analysis; pertinent authors were from 22 countries covering five continents. We identified three key thematic clusters in the published literature: Cluster 1) Medico-scientific contributions with the participation of military medical personnel or institutions: members of the military acted as subject matter experts, clinical and experimental (co-) investigators as well as co-founders for enabling COVID-19 relevant research. Areas covered were relevant to the COVID-19 patient’s clinical journey from prevention, exposure, diagnostics, and treatment and included pertinent fields such as digital health and telemedicine, global and public health, critical care, emergency and disaster medicine, radiology, neurology, as well as other medical specialties, i.e., respiratory care, pulmonology, burn medicine, and transfusion medicine, in addition to environmental and occupational sciences as well as materials science. Cluster 2) CIMIC field experiences or analyses included areas such as political framework, strategy, structure, nature of civil-military interaction and concrete mission reports in selected countries. Themes covered a broad spectrum of pandemic disaster management subjects such as capacity and surge capacity building, medical and pharmaceutical logistics, patient care under austere circumstances, SARS-CoV-2 testing support, intelligent and innovative information management, vaccination support, and disaster communication. Cluster 3) The military as a role model for crisis management. Conclusion: civil-military cooperation made a significant contribution to the level of resilience in crisis management on a global scale, positively impacting a broad spectrum of core abilities during the COVID-19 pandemic.